Stent dilatation of atretic aortic coarctation in an adult-case report and literature review. Issue 1 (December 2016) - Jha, Neerod; Tofeig, Magdi; Kumar, Rajappan; ElTahir, Amin; Athar, Syed; AlHakami, Aref; Khan, Arshad; Khan, Mohammad
Abstract Background Patients with functional aortic interruption of the descending thoracic aorta at the isthmus due to severe coarctation in association with atretic lumen are extremely rare in the adult population. The management is challenging and carries high morbidity and mortality. Case presentation We describe successful percutaneous reconstruction using a covered stent in a similar patient who is doing well two-years after intervention. A literature search was done to explore management strategies and their long-term outcomes for better understanding. Conclusions This report is an attempt to highlight the role of minimal invasive approach in the management of rare, severe coarctation of the aorta in adult patients to avoid morbidity and mortality associated with more invasive procedures.